Expression of histone variant, H2A.1 is associated with the undifferentiated state of hepatocyte. (October 2014) - Tyagi, Monica; Khade, Bharat; Khan, Shafqat A; Ingle, Arvind; Gupta, Sanjay
Recent studies suggest the incorporation of histone variants into the chromatin regulate cellular proliferation, differentiation, and de-differentiation. We have earlier reported the increase of H2A.1 variant during sequential de-differentiation of hepatocyte to hepato-cellular carcinoma. Here, we decipher the alterations in expression of H2A.1 and H2A.2 variants during rat liver embryogenesis and regeneration. The expression of H2A.1 and H2A.2, at protein and mRNA level, does not alter in normal cellular proliferation associated with regeneration of liver post PH. In contrast, gradual decrease of H2A.1 with increase of H2A.2 is observed during differentiation of embryonic to adult liver. Furthermore, the accumulation of H2A.1 is higher in embryonic stem cells compared to normal adult liver. Collectively, these data support a strong correlation of H2A.1 expression with undifferentiated cells and overall epigenetic reprogramming in dedifferentiation and maturation of undifferentiated cells, rather than with normal cellular proliferation.